GE_GERICHTE C/3896/2017 vom 30. Januar 2018 - GE Cour de justice (2018)
DÉBITEUR ; DIRECTIVE(INJONCTION) ; OBLIGATION D'ENTRETIEN ; PROTECTION DE L'UNION CONJUGALE ; FORMALISME EXCESSIF ; DÉCISION ÉTRANGÈRE | LDIP.27; LDIP.29.al1.leta; LDIP.29.al1.ch2; LDIP.29.al3; LDIP.85.al1; CC.177; CPC.84.al2; CLaH.96.al5